COVID-19 in Renal Transplantation - Derakhshan, Ali (Journal of Pediatric Nephrology, 2020)
During the end of 2019 a group of patients with pneumonia were described in Wuhan city of china with progression to ARDS with variable outcome. Mortality rate was higher in the oldest and in those with comorbid conditions. Kidney transplant recipients as a group of immunocompromised hosts are believed to be a high risk group in case of infection by SARS-CoV-19 virus with unfavorable outcome. On the other hand cytokine storm with its severe inflammatory response as a major risk factor of mortality may be prevented by ongoing immunosuppressive therapy .Our knowledge about the pathophysiology and treatment options of COVID-19 in kidney transplant recipients are growing on daily bases and at the time being is derived mainly from the few published case reports, reviews and some society guidelines in the published literature.